A facile oxygen-17 NMR method to determine effective viscosity in dilute, molecularly crowded and confined aqueous media. Issue 82 (30th September 2019) - Rezaei-Ghaleh, Nasrollah; Munari, Francesca; Becker, Stefan; Assfalg, Michael; Griesinger, Christian
Abstract : This NMR probe of water dynamics enables viscosity determination in concentrated and crowded solutions and allows quantifying internal fluidity within biological condensates. Abstract : We present an NMR method based on natural abundance 17 O relaxation of water to determine effective viscosity in biological aqueous samples. The method accurately captures viscosity of dilute and crowded protein solutions and offers a fairly simple way to quantify the internal fluidity of biological condensates formed through phase separation.